Occurrence of persistent organic pollutants and polycyclic aromatic hydrocarbons in sediments of the inner bay of Lake Titicaca (Puno, Peru) - Zamalloa Cuba, Walter Alejandro (2020)
Lake Titicaca is an important water resource and the ecological balance of the Peruvian-Bolivian Andean plateau depends on it. At present, it is being disturbed by poor water resource management practices, which is why persistent organic pollutants (POPs) and polycyclic aromatic hydrocarbons (PAHs) were monitored in sediments from 13 sampling stations in the Inner Bay of Lake Titicaca (Puno, Peru). The samples were lyophilized and stored at -70°C for further analysis. For the validation of the analytical method, the following parameters were considered: recovery, repetition and uncertainty of all the compounds studied. The POPs were determined by gas chromatography coupled to an electron capture detector, and the presence of β-BHC, 0.018 μg/g; o,p´-DDE, 0.0011 μg/g; dicofol 0.0065 μg/g and endosulfan sulfate 0.0061 μg/g were detected. On the other hand, PAHs were determined by liquid chromatography coupled to a fluorescence detector, confirming the presence of naphthalene, 0.058 μg/g; pyrene, 0.039 μg/g; benzo(a)anthracene, 0.571 μg/g and chrysene, 0.033 μg/g. The presence of POPs and PAHs evidences an environmental risk for the species that inhabit the ecosystem of this lake.